ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN PRODUK KEUANGAN SYARIAH - Fiska Handayani Putri; Randa Kurnia R, Nur Jannah Hasibuan, Dwi Imanda, Rudi Ardiansyah, Anggia Lorenza, Syifa Mahira (BORJUIS: JURNAL OF ECONOMY, 2023)
Consumer decisions, analyzed through marginal utility theory, consumer satisfaction, and consumer purchasing decision models, involve the steps in purchasing a product or service. Theories such as involvement bonds, anticipation and social position, consumer behavior, attitude formation, personal factors, social comparison, and family purchasing decisions enrich the understanding of consumer decision dynamics. In the context of Islamic financial products, factors such as religion, belief, comfort, knowledge and economic aspects play a role. Religious beliefs encourage the choice of sharia products, while satisfaction and service quality maintain consumer loyalty. Financial knowledge and education increases consumer awareness of sharia products, while economic factors such as prices and costs influence consumer decisions. Effective promotion and marketing supports consumer awareness and interest in Islamic financial products, enables financial institutions and marketers to design effective strategies, meets consumer needs, and supports the growth of the Islamic financial industry.